ROLE PLAY IN ENGLISH FOR HOTEL AND TOURISM: BENEFITS AND ISSUES IN THE IMPLEMENTATION - Muliana, I Wayan (Pusat penelitian & Pengabdian Kepada Masyarakat STP Nusa Dua Bali, 2011)
English for Specific Purposes (ESP) for Hotel and Tourism industry has a characteristic of emphasizing communicative competence over other competences. The articles main aim is to increase the awareness of the importance of role play activities in bringing real life situations into the classroom so that it provides ideal communicative opportunity to the students. It also discusses some issues related to the benefits of using role play: integrating learning materials with the methodology of the vocational class, increasing the students' motivation, and integrating the language skills. The article is also to define what we mean by role play, to discuss some common questions/problems in using role play, to review some role plays in several course books of ESP for hotel and tourism and to suggest some adaptations to match it with the students 'future job experience.